2015
DOI: 10.1128/jcm.01495-15
|View full text |Cite
|
Sign up to set email alerts
|

Commutability of the First World Health Organization International Standard for Human Cytomegalovirus

Abstract: Quantitative detection of cytomegalovirus (CMV) DNA has become a standard part of care for many groups of immunocompromised patients; recent development of the first WHO international standard for human CMV DNA has raised hopes of reducing interlaboratory variability of results. Commutability of reference material has been shown to be necessary if such material is to reduce variability among laboratories. Here we evaluated the commutability of the WHO standard using 10 different real-time quantitative CMV PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 19 publications
0
60
1
3
Order By: Relevance
“…53 In the fi eld of HIV/AIDS, viral load determination has become a routine test and is the basis of clinical patient management. 54 Although the commutability of some materials might need additional work to yield consensus, 55 clearly these eff orts have a positive eff ect on comparability between assays. 56 Eff orts towards standardising fi lovirus assays hold the promise of similar eff ects and should be vigorously pursued.…”
Section: Personal Viewmentioning
confidence: 99%
“…53 In the fi eld of HIV/AIDS, viral load determination has become a routine test and is the basis of clinical patient management. 54 Although the commutability of some materials might need additional work to yield consensus, 55 clearly these eff orts have a positive eff ect on comparability between assays. 56 Eff orts towards standardising fi lovirus assays hold the promise of similar eff ects and should be vigorously pursued.…”
Section: Personal Viewmentioning
confidence: 99%
“…The reason for the differing commutability between the WHO and ABI material is uncertain. Previous work has shown limitations in commutability utilizing WHO standards (21). Here, both standards were whole-virus preparations, but one still showed behavior more like clinical samples.…”
Section: Discussionmentioning
confidence: 92%
“…Noncommutable standards may actually worsen the divergence of results between assays rather than improving agreement (14). Recent work has indicated that not all assays show the same degree of commutability with WHO standards (15,16). This may not reflect an intrinsic problem with the WHO material but rather greater or lesser compatibility with specific constellations of sample preparation, target sequences, primers, probes, amplification conditions, and other variables that might alter the consistent relationship between how clinical samples and standards behave in a given assay system.…”
Section: Resultsmentioning
confidence: 99%